An Analysis of Hybrid Energy Modelling (Grid and Inverter Based Resources) Using Grid Following Inverter for the Integration of Renewable Energy Generation - Mujtahida, Fikarul; Rahmania Putri Ramadhani; Prisma Megantoro; Mohammed Mareai; Muhammad Akbar Syahbani (Journal of Advanced Technology and Multidiscipline, 2024)
The energy dependency of the grid will cause its own problems because the energy generated comes from fossil fuels. On the other hand, centralized electrification using renewable energy has a high risk on frequency and voltage stability. Renewable energy depends entirely on climate conditions and has no inertia to maintain stability. Hybrid energy between grids and Inverter Based Resources (IBRs) are alternative solutions used. The research applies an inverter control scheme to IBRs to be penetrated the grid. The research will apply a zero-export load with electricity requirements to be charged to renewable power plants using grid distribution networks. The inertia less properties of renewable energy will cause interference when combined with the power grid (synchronous generator). It will also be analyzed on this study by applying the following inverter scheme by paying attention to the phase angle and synchronization against the voltage, current and frequency variables of the grid. The results obtained in this study; renewable energy can contribute 90% to the load. This is due to the Losses factor and efficiency system in the plant. Renewable energy generators feed active power to the grid as well as support grids with a Total Harmonic Distortion (THD) indicator of <10%. In the design of this hybrid power system, it is done on MATLAB software with installation configuration in accordance with IEEE standards so that it can be a reference for the installation of real-condition renewable energies with grid. Keywords—Renewable Energy, Grid Following, Green Electricity, Hybrid Energy